Cost-Utility Analysis of CTEV Treatment by Ponseti Method in Siaga Utama Orthopedic Hospital - Zubaidi, Muhammad Nasir; Pribadi, Firman (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Congenital talipes equinovarus (CTEV), or true clubfoot, is a foot deformity. The incidence of CTEV varies depending on race and gender. Traditionally, surgical intervention has been the treatment of choice for CTEV at a considerable cost. The Ponseti is a CTEV treatment method that does not use surgery and anesthesia. Instead, it uses gentle manipulation to correct the deformity. It is also more affordable than surgical treatment. Therefore, this study aims to explain the Effect of CTEV Treatment Costs with the Ponseti Method on Patient Quality of Life at Siaga Utama Orthopedic Hospital. This study uses quantitative methods. This study used a retrospective study with a sample of CTEV patients at Siaga Utama Orthopedic Hospital from February 2022 - February 2023. The author examined the effect of CTEV treatment costs on quality of life (QALYs). The results showed that the cost of treatment with the onset method positively impacted the patient's quality of life. The cost of treatment with the Ponseti method proved to be cheaper. However, it can vary depending on many factors, such as location, type of disease or condition, the severity of the situation, and so on. In addition, the Ponseti method is time-consuming and requires specialized skills from the therapist to achieve optimal results.